The Theory of the Top. Volume IV Technical Applications of the Theory of the Top - Klein, Felix; Sommerfeld, Arnold (Springer New York : Imprint: Birkhäuser, 2014)
The Theory of the Top. Volume IV. Technical Applications of the Theory of the Top is the fourth and final volume in a series of self-contained English translations of the classic and definitive treatment of rigid body motion. Key features: * Complete and unabridged presentation with recent advances and additional notes; * Annotations by the translators provide insights into the nature of science and mathematics in the late 19th century; * Each volume interweaves theory and applications. The Theory of the Top was originally presented by Felix Klein as an 1895 lecture at Göttingen University that was broadened in scope and clarified as a result of collaboration with Arnold Sommerfeld.  Graduate students and researchers interested in theoretical and applied mechanics will find this series of books a thorough and insightful account.  Other volumes in the series include Introduction to the Kinematics and Kinetics of the Top, Development of the Theory in the Case of the Heavy Symmetric Top, and Perturbations.  Astronomical and Geophysical Applications.